The Effect of Fines and Temperature on the Mode I Fracture Characteristics of the Frozen Sand - Bumsik Hwang; Wanjei Cho (Advances in Civil Engineering)
In this research, the three-point bending tests were conducted using frozen sand specimen of 0, 5, 10, and 15% fine contents with specified notch under −5, −10, and −15°C condition to analyse the effects of fine contents and temperature on the mode I fracture characteristics of the frozen sand. Three-point bending tests were performed using the standard test method of other materials such as metal and concrete. In order to investigate the effect of fine and temperature on the fracture characteristics of the frozen sand, the stress intensity factor and fracture energy were calculated using three-point bending test results. Based on the test results, fine contents and temperature can affect the brittle and ductile responses of the frozen sand. Furthermore, the fracture toughness of frozen sand increase with the fine contents’ increase and the temperature decrease. Fracture energy required for the crack initiation can be dominated by the fracture behaviour and brittle and ductile response.